Forming and centering : foundational aspects of architectural design - Moffett, Kenneth M. (Emerald Publishing, 2017)
"Nearly every work of architecture can be characterized by specific approaches to forming and centering. An awareness of these 'underpinnings' would facilitate a more informed approach to architectural design problems, as well as a deeper understanding of the central issues (and flaws) embodied by completed works of architecture. But the addressing of such topics has generally remained multifarious and diverse: more in the nature of a collection of independent issues than an overarching analytical argument. In this book, fresh looks at such issues are assembled and recast into a fully integrated narrative, based on two foundational and complementary aspects of architectural design: those that give shape and those that give focus--forming and centering."--Provided by publisher.